Infrastructure and urbanization in the People's Republic of China - Zhigang Li (Asian Development Bank Institute (ADBI), 2017)
The recent experience of infrastructure investment in the People's Republic of China (PRC) suggests an intertwined relationship between investment, urbanization, and economic growth. In one mechanism, urbanization generates demand for infrastructure investment, which then drives economic growth via various channels including reducing transaction costs and raising productivity. Another mechanism emphasized in this paper is that infrastructure investment can promote urbanization through facilitating economic agglomeration toward hub cities. This agglomeration process also raises productivity in the economy. The lessons from the PRC have implications for infrastructure financing. On the one hand, recent reforms have allowed the market to play an increasingly important role in funding infrastructure investment, helping improve the efficiency of infrastructure investment and the productivity of the economy. On the other hand, evidence in the PRC suggests a cross-province spillover effect of road infrastructure, supporting the central government's role in infrastructure financing. Although the current infrastructure investment system is still distorted by local governments' incentives and decisions, there is no evidence of over-investment in infrastructure at the aggregate level. Nevertheless, there is strong evidence that the marginal return to infrastructure investment in the PRC has been rapidly declining. Hence, it is urgent for policy makers to reform the existing system to base their investment decisions on the economic returns to infrastructure. The interregional flow of goods and production factors (labor and capital) is a fundamental force that drives urbanization, but the market may not be efficient in financing and infrastructure construction. This paper analyzes infrastructure-related institutions and the interrelation between infrastructure and urbanization. It addresses the following issues: What is the relationship between infrastructure, growth, and urbanization? How efficient have investment and financing been for infrastructure construction? How can we evaluate the performance of infrastructure development? How and to what extent should the government be involved in infrastructure construction?
Keywords: H54; O18; R42; 330; infrastructure; urbanization; infrastructure financing; development; construction; investment; economic growth